Palestine and israel: impact of 73 years of colonialism, apartheid and genocide - Gontijo, Luísa; Vilella, Amanda; Pinho, Rafaela; Reyes, Angíe; Almassri, Nasrallah; Silva, Raquel (Brazilian Journal of Global Health, 2021)
OBJETIVO: A ocupação da Palestina foi estruturada por meio de um discurso colonialista e orientalista. Desde 1948, as políticas israelenses geraram uma ampla gama de abusos contra os palestinos. Esse trabalho objetivou analisar os impactos na saúde e qualidade de vida dos palestinos decorrentes da ocupação israelense. MÉTODOS: Revisão narrativa da literatura sobre os impactos causados pela ocupação israelense na saúde e na qualidade de vida dos palestinos. RESULTADOS: A Palestina tem 2,45 milhões de pessoas que requerem alguma forma de assistência humanitária. A situação atual se deve à constante invasão dos territórios palestinos por assentamentos judeus e ao rígido controle dos territórios conquistados, o que impede a população de ter acesso a direitos básicos como saúde e alimentação. CONCLUSÃO: A ajuda humanitária internacional não será suficiente para minimizar a desigualdade vivida na região, que é causada pelo contexto político de colonialidade e Apartheid da região. DESCRITORES: Palestina, Impactos na saúde, Colonialidade; Apartheid, Genocídio, Assistência humanitária. ABSTRACT OBJECTIVE: Occupation of Palestine was structured through a colonialist and orientalist discourse. Since 1948, Israeli policies have generated a wide range of abuses against Palestinians. This work aimed to analyze the impacts on the health and quality of life of Palestinians resulting from the Israeli occupation METHODS: Narrative Review of literature about impacts caused by the Israel occupation on Palestinians’ health and quality of life. RESULTS: Palestine has 2.45 million people that requires some form of humanitarian assistance. The current situation is due to constant invasion of Palestinian territories by Jewish settlements and the rigid control of conquered territories, which prevents the population from accessing basic rights such as health and food. CONCLUSION: International humanitarian aid will not be enough to minimize the inequality experienced in the region, which is caused by the political context of coloniality and apartheid in the region. DESCRIPTORS: Palestine, Health Impacts, Coloniality, Apartheid, Genocide, Humanitarian Assistence.